2020
DOI: 10.1038/s41560-020-00683-8
|View full text |Cite|
|
Sign up to set email alerts
|

Patenting and business outcomes for cleantech startups funded by the Advanced Research Projects Agency-Energy

Abstract: Innovation to reduce the cost of clean technologies has large environmental and societal benefits, and governments can play an important role in helping cleantech startups innovate and overcome risks involved in technology development. Here we examine the impact of the U.S. Advanced Research Projects Agency -Energy (ARPA-E) on two outcomes for startup companies: innovation (measured by patenting activity) and business success (measured by venture capital funding raised, survival, and acquisition or initial pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 59 publications
(57 reference statements)
1
16
0
Order By: Relevance
“…The study project (IRB number 1635964-1) has been reviewed and determined to meet the following federal exemption category per 45 CFR 46.104d: Exemption Category: 2 (ii) (2) Research that only includes interactions involving educational tests (cognitive, diagnostic, aptitude, achievement), survey procedures, interview procedures, or observation of public behavior (including visual or auditory recording) if at least one of the following criteria is met: (ii) Any disclosure of the human subjects' responses outside the research would not reasonably place the subjects at risk of criminal or civil liability or be damaging to the subjects' financial standing, employability, educational advancement, or reputation; This determination is based on no greater than minimal risk to research participants. When a research project is determined to meet the criteria for an exempt status, it means the project as submitted is exempt from Michigan Technological Institutional Review Board (MTU-IRB) oversight and does not require annual continuing review.…”
Section: Institutional Review Board Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…The study project (IRB number 1635964-1) has been reviewed and determined to meet the following federal exemption category per 45 CFR 46.104d: Exemption Category: 2 (ii) (2) Research that only includes interactions involving educational tests (cognitive, diagnostic, aptitude, achievement), survey procedures, interview procedures, or observation of public behavior (including visual or auditory recording) if at least one of the following criteria is met: (ii) Any disclosure of the human subjects' responses outside the research would not reasonably place the subjects at risk of criminal or civil liability or be damaging to the subjects' financial standing, employability, educational advancement, or reputation; This determination is based on no greater than minimal risk to research participants. When a research project is determined to meet the criteria for an exempt status, it means the project as submitted is exempt from Michigan Technological Institutional Review Board (MTU-IRB) oversight and does not require annual continuing review.…”
Section: Institutional Review Board Statementmentioning
confidence: 99%
“…The type of energy technology used is central in the climate discussion, due to the variety of sources from where energy is harnessed and the associated emissions from each energy technology used. In addition, the types of energy technology used have been linked to socioeconomic and environmental outcomes of individual and community wellbeing [1,2]. Massive deployment of alternative emerging technologies, such as renewable electricity (RE), is critical to achieving the desired stability of the atmospheric CO 2 concentration [3] and it also offers economic benefits [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Victor highlighted programs like ARPA-E and DARPA as programs with proven processes that identify potential successes and failures and manage projects accordingly. ARPA-E has funded projects on processes ranging from engineered biofuel crops to the conversion of CO 2 to liquid fuel ( ARPA-E, 2017 ), and a National Academies evaluation of ARPA-E found that APRA-E-recipients were approximately 60% more-likely to publish than those receiving funding from DOE’s Office of Science, and 13% of ARPA-E awards had resulted in a patent, compared with 5% of projects receiving funding from DOE’s Office of Energy Efficiency & Renewable Energy ( NASEM, 2017b ).A recent quantitative analysis found ARPA-E to be fulfilling its objective of supporting the development of innovative energy technologies – ARPA-E-funded start-ups file patents at twice the rate of comparable clean energy technology companies ( Goldstein et al., 2020 ). Noting that the success of programs cannot be determined by one single metric, a National Academies evaluation assessed the agency from a more holistic perspective including patents, publications, follow-on funding, and the foundation of new firms.…”
Section: Taking On a Greater Quantity Of Risk In The Federal Governme...mentioning
confidence: 99%
“…When providing later-stage funding, we find that public investors have not fared worse than their private-sector counterparts, and may improve chances for exit if one assumes that public funding goes to startups less likely to attract late round private funding on their own. Here, our comprehensive data including companies in multiple sectors provides additional context compared to earlier studies focusing solely on public investments in the energy sector (e.g., Howell (2017) and Goldstein et al (2020)). Since venture capital investments in clean energy as a whole perform much worse than in other sectors, simply matching private sector performance in the clean energy sector is not enough.…”
Section: Introductionmentioning
confidence: 99%